Diversity and Conservation Gap Analysis of the Solanaceae of Southern South America - Moreira-Muñoz, Andrés; Palchetti, María Virginia; Morales-Fierro, Vanezza; Duval, Valeria Soledad; Allesch-Villalobos, Rudy; González-Orozco, Carlos E. (Frontiers in Plant Science, 2022)
There is a need to make substantial advances in the taxonomic, systematic and distribution knowledge of plants, and find better ways of transmission of this information to society to surpass the general pattern described as “plant blindness”. The diversity of the plant family Solanaceae reaches its peak in South America, however many of its species are threatened due to the expansion of the human footprint. Here we examine the diversity patterns of the family in southern South America (Argentina and Chile) by means of species richness (SR), weighted endemism (WE) and corrected weighted endemism (CWE). We also evaluate conservation gaps in relation to protected areas and the human footprint as a proxy for potential impacts on this biodiversity. Results show two richness centers in NW and NE Argentina, with a high degree of overlap with protected areas, which on the other side show a relative high index of human footprint. Comparatively, coastal Atacama (Chile) shows lower richness values, but outstanding CWE and WE values. The coast of Atacama harbors high values due the presence of species of the genus Nolana with restricted distributions. Protected areas in this tight coastal strip are sparse, and the human footprint is also relatively high. The degree of protection based on these parameters is then unbalanced, highlighting the need for a geographically explicit strategy for the conservation of the family at subcontinental scale. In doing so, it is likely that other representatives of these unique centers of richness and endemism will benefit.